2022
DOI: 10.3390/jcm11030713
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Risk of Nodal Involvement in Rectal Neuroendocrine Neoplasms: The NOVARA Score, a Multicentre Retrospective Study

Abstract: Rectal neuroendocrine tumors (r-NETs) are rare tumors with overall good prognosis after complete resection. However, there is no consensus on the extension of lymphadenectomy or regarding contraindications to extensive resection. In this study, we aim to identify predictive factors that correlate with nodal metastasis in patients affected by G1–G2 r-NETs. A retrospective analysis of G1–G2 r-NETs patients from eight tertiary Italian centers was performed. From January 1990 to January 2020, 210 patients were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In our recent study [ 29 ], tumor size greater than 15 mm was considered to be an independent risk factor for lymph node metastasis in patients with colorectal neuroendocrine neoplasm, so 15 mm was used as the cut-off value to study the difference in endoscopic resection methods. We noticed that a recent report [ 30 ] suggested that tumor size greater than 11.5 mm was independent risk factor for lymph node metastases in patients with R-NETs. Maybe it's because of the different databases or the differences between the eastern and western populations.…”
Section: Discussionmentioning
confidence: 83%
“…In our recent study [ 29 ], tumor size greater than 15 mm was considered to be an independent risk factor for lymph node metastasis in patients with colorectal neuroendocrine neoplasm, so 15 mm was used as the cut-off value to study the difference in endoscopic resection methods. We noticed that a recent report [ 30 ] suggested that tumor size greater than 11.5 mm was independent risk factor for lymph node metastases in patients with R-NETs. Maybe it's because of the different databases or the differences between the eastern and western populations.…”
Section: Discussionmentioning
confidence: 83%
“…The rectal NEN with a maximum diameter of 1-2 cm has a lymph node metastasis rate of about 30% at the time of diagnosis, and about 40% in those ≥20 mm ( 27 , 34 ). In the latest multicenter retrospective study, diameter > 11.5 mm and vascular infiltration were independently correlated with nodal involvement ( 35 ). It is reported that 22.7% of patients with multiple rectal NETs whose diameter is less than 10mm have lymphatic metastasis ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors for metastatic disease such as the presence of lymphovascular invasion, the presence of muscular invasion, histological non‐ L cell‐type and a high tumour grade have also been reported in different studies 9,29,31,35,36 . Correlation between tumour size and lymphovascular invasion has also been demonstrated with a tumour size ≥5 mm at higher risk of lymphovascular involvement than in tumours with a size <5 mm, 36 and predictive scores taking into account both, the tumour size and the lymphovascular involvement have been shown to provide an accurate assessment of the risk of metastatic lymph node involvement 37,38 …”
Section: Introductionmentioning
confidence: 90%
“…9,29,31,35,36 Correlation between tumour size and lymphovascular invasion has also been demonstrated with a tumour size ≥5 mm at higher risk of lymphovascular involvement than in tumours with a size <5 mm, 36 and predictive scores taking into account both, the tumour size and the lymphovascular involvement have been shown to provide an accurate assessment of the risk of metastatic lymph node involvement. 37,38 Computed tomography (CT) has limited value for the detection and characterisation of regional metastatic lymph nodes in patients with rNET. 39 Similarly to rectal adenocarcinoma, MRI with diffusionweighted imaging (DWI) is considered as the most sensitive imaging method for regional lymph node detection, detection of residual disease after incomplete resection, and the involvement of pelvic structures in more advanced tumours.…”
Section: Introductionmentioning
confidence: 99%